Maham ka ghubara:bachon ke liye kahaniyon ka silsila: hum chaand sitarey - Syed, Wadood Shah (Children Publication Lahore, 2020)
This captivating children's book, written in simple Urdu, takes young readers on a delightful journey. The story is filled with colorful illustrations and easy-to-understand language, perfect for early readers.